Governança como condição sine qua non: conexões entre degradação ambiental e pobreza na ASD dos sertões dos Inhamuns - Caetano, Francisco Aquiles de Oliveira (2023)
The thesis to be defended addresses the relationship between governance, poverty and environmental degradation. It is assumed that governance has a significant impact on reducing environmental degradation, however this impact is influenced by the existing poverty in rural communities. Therefore, the study aims, in general, at the existing relationships between the principles of governance, environmental degradation and poverty in rural communities inserted in the ASD of the sertões dos Inhamuns, in the State of Ceará. The research uses secondary data and was carried out between December 2017 and January 2018, in the municipalities of Arneiroz, Tauá and Independência. The work was developed in order to characterize the dimensions of the study, in rural communities inserted in the Inhamuns ASD, and to describe the causality between them through the structuring of aggregated indices: Multidimensional Poverty Index (MPI), Governance Index (IG) and Environmental Degradation Index (IDA). Furthermore, Path Analysis, a statistical methodology used to estimate and describe the directed dependencies between sets of variables, was used. It was possible to observe, through the PER (Pressure/State/Response) indicators for environmental degradation, that the communities present factors that characterize anthropic action on the environment, motivated mainly by the search for better living conditions. The poverty observed in communities interacts with environmental issues, so that communities with higher rates of poverty correspond to higher rates of environmental degradation. Governance, through the subindices that compose it, proved to be at low levels, insufficient to promote considerable changes in installed poverty and degradation. It was observed that poverty exerts a moderating effect that interferes with the overall effect of governance on environmental degradation.